Anton Webern's Six Pieces for Orchestra: A Comparison of the Two Published Versions - Falck, Robert (Canadian University Music Review / Revue de musique des universités canadiennes, 1993)
There are two published versions of Anton Webern's Six Pieces for Orchestra, though the composer considered the 1928 revision to be the only valid one. The 1909 version was first performed in 1913, but in spite of at least two projected performances, the composer may never had heard the revision. Although the revision was not carried out for a specific performance, the ostensible motivation for it was to reduce the rather excessive orchestral demands of the first version, and thus make it more practical for performance. While many of the revisions do result from the reduced orchestration, there are many changes in dynamics, tempo, phrasing and instrumental emphasis which do not. In fact, the new score is a thorough rehearing of the pieces, and the revisions affect everything from their overall formal conception to often very subtle relationships among the elements of the individual movements. The revisions also reflect the changes both in Webern's personal style between 1909 and 1928, the year of the Symphonie, op. 21, but also the global change from the luxuriant and indulgent post-romantic style to the "lean, athletic" style of Neoclassicism.